ANALISIS HUBUNGAN DEWAN KOMISARIS INDEPENDEN, VOLUNTARY DISCLOSURE, FIRM SIZE DAN COST OF DEBT - Nurdiniah, Dade; Munandar, Agus (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to analyze the relationship of the independent board of commissioners, voluntary disclosure, and firm size to the cost of debt. Design/methodology/approach- The population of this research is property and real estate companies listed on the Indonesia Stock Exchange in 2014-2016. The method of selecting samples using purposive sampling criteria. The analytical method in this study is multiple linear regression analysis. Findings- The results showed that the independent board of commissioners and firm size had no effect on the cost of debt while voluntary disclosure had a negative effect on the cost of debt. Limitations- Limitations in this study: (1) this study only uses property and real estate companies as research objects listed on the Indonesia Stock Exchange; (2) The study period is only 3 (three) years as a sample; and (3) the variables in this study are only three independent variables. Keywords: Independent board of commissioners, Firm size, Voluntary disclosure, Cost of debt.